2005
DOI: 10.1301/nr.2005.dec.s109-s115
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Iron-Folic Acid Supplementation to Improve Iron Status and Prevent Pregnancy Anemia in Filipino Women of Reproductive Age: The Philippine Experience through Government and Private Partnership

Abstract: With the participation of the government and private sectors in the Philippines, weekly iron-folic acid supplementation introduced within a social marketing framework and a social mobilization campaign successfully improved knowledge and practice of buying and regularly taking supplements by women of reproductive age, both pregnant and non-pregnant. Adolescent girls in school were also active participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The Cambodian programme was implemented in three different environments (secondary school girls, women working in garment factories and women in rural villages) and found that all three groups of reproductive-aged women showed substantial improvements in knowledge about the causes, consequences and prevention of anaemia (36) . In the Philippine programme (37)(38)(39) , knowledge and practice of buying and regularly taking supplements by reproductive-aged women were both improved. Although Hb levels showed minimal change, serum ferritin and haematocrit increased significantly.…”
Section: Study Resultsmentioning
confidence: 99%
“…The Cambodian programme was implemented in three different environments (secondary school girls, women working in garment factories and women in rural villages) and found that all three groups of reproductive-aged women showed substantial improvements in knowledge about the causes, consequences and prevention of anaemia (36) . In the Philippine programme (37)(38)(39) , knowledge and practice of buying and regularly taking supplements by reproductive-aged women were both improved. Although Hb levels showed minimal change, serum ferritin and haematocrit increased significantly.…”
Section: Study Resultsmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Nevertheless, supplementation is the most widely employed strategy to alleviate iron deficiency, both globally and locally. 3,35 Women take IFAS during pregnancy to prevent specific micronutrient deficiencies under the programs provided by the government of the Philippines. 3,35,36 In the Philippines, Patient-level care is provided at widely utilized barangay (village) health stations (BHS) that are operated by trained midwives.…”
Section: Introductionmentioning
confidence: 99%
“…3,35 Women take IFAS during pregnancy to prevent specific micronutrient deficiencies under the programs provided by the government of the Philippines. 3,35,36 In the Philippines, Patient-level care is provided at widely utilized barangay (village) health stations (BHS) that are operated by trained midwives. The midwife in each BHS identified all the pregnant women who had received IFAS from that BHS during their pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons Honduras would benefit more from the implementation of a cost-effective preconceptional folic acid supplementation programme that would reach the poor urban and rural high-risk populations. Recently, the regional office of the WHO in South Asia (Philippines, Cambodia and Vietnam) published results on community trials assessing the effectiveness of micronutrient supplementation to the population with a pill containing both Fe and folic acid (37)(38)(39)(40)(41)(42) . The strategy tailored the supplementation intervention and market strategy to each country's culture and values.…”
Section: Discussionmentioning
confidence: 99%